China on Film : a Century of Exploration, Confrontation, and Controversy. - Pickowicz, Paul (Rowman & Littlefield Publishers, 2011)
Leading scholar Paul G. Pickowicz traces the dynamic history of Chinese filmmaking and its stunning development decade-by-decade since the 1920s. During the last one hundred years, China has been embroiled in a seemingly unending series of wars, revolutions, and jarring social transformations. Despite daunting censorship obstacles, Chinese filmmakers have found ingenious ways of taking poli.